1995
DOI: 10.1002/anie.199424681
|View full text |Cite
|
Sign up to set email alerts
|

Novel Bimetallic Model System for Cytochrome P450: Effect of Membrane Environment on the Catalytic Oxidation

Abstract: A novel membrane‐bound cytochrome P450 mimic (shown schematically below, 1: a RhIII complex, 2: a manganoporphyrin) catalyzes the epoxidation of alkenes with dioxygen. The turnover numbers achieved with this catalyst are in the same range as those obtained with the natural enzyme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…This reflected the cooperative nature of the active sites within the catalyst which cleaved simultaneously several ester bonds of the polymeric DNA backbone. 492,493 The groups of Groves 494 and Nolte 70,[495][496][497][498] employed synthetic vesicles as a medium for oxidation reactions. Schenning et al reported a cytochrome P450 mimic which combined (i) a synthetic phospholipid vesicle, (ii) a metallo-porphyrin catalyst 90 trapped in the membrane of these vesicles, (iii) an axial-ligand (N-methylimidazole), (iv) a combination of a Rh(III) complex 91 and formate anions as a reducing agent, and (v) molecular oxygen (Fig.…”
Section: Catalysis In Micelles and Vesiclesmentioning
confidence: 99%
“…This reflected the cooperative nature of the active sites within the catalyst which cleaved simultaneously several ester bonds of the polymeric DNA backbone. 492,493 The groups of Groves 494 and Nolte 70,[495][496][497][498] employed synthetic vesicles as a medium for oxidation reactions. Schenning et al reported a cytochrome P450 mimic which combined (i) a synthetic phospholipid vesicle, (ii) a metallo-porphyrin catalyst 90 trapped in the membrane of these vesicles, (iii) an axial-ligand (N-methylimidazole), (iv) a combination of a Rh(III) complex 91 and formate anions as a reducing agent, and (v) molecular oxygen (Fig.…”
Section: Catalysis In Micelles and Vesiclesmentioning
confidence: 99%
“…In DHP and DODAC vesicles, manganese tetradichlorephenylporphyrin acetate (MnTDCPP acetate), an amphiphilic rhodium complex, and N-methylimidazole ( Figure 14) were introduced. 169 Detailed mechanistic studies revealed that the reduction of the Rh(III) is fastest in DODAC vesicles, likely the result of an increased concentration of the negatively charged formate ions at the positively charged vesicle surface. Consequently, also the reduction of the mangenese porphyrin incorporated in the vesicle bilayer was the fastest in DODAC vesicles.…”
Section: Reactions In or At The Vesicle Membranementioning
confidence: 99%
“…Nolte and co-workers have incorporated hydrophobic manganese porphyrins into vesicles in which electrons were provided by the oxidation of either hydrogen with colloidal Platinum 8 or formate at rhodium complexes 9 10 . Other systems also used manganese porphyrins in combination with either nicotinamide and benzoic anhydride 11 , or pyruvate oxidase and flavin cofactors 12 .…”
mentioning
confidence: 99%